Nursing experience with pneumonia patients based on visual reality simulation: a qualitative study - Soomin An; Youn-Joo Um (BMC Nursing)
Abstract Background Clinical experience is crucial for nursing students. However, opportunities for hands-on care, especially in complex conditions such as pneumonia, are limited. Virtual reality (VR) offers a solution simulating real-world patient care scenarios. This study explored nursing students’ experiences and perceptions of using virtual reality (VR) in the nursing care of patients with pneumonia. It sought to identify the benefits and challenges of integrating VR into nursing education to enhance clinical competencies in managing pneumonia. Additionally, it provides recommendations for improving nursing education to ensure that future nurses gain sufficient experience in caring for patients with pneumonia. Methods This qualitative descriptive study involved 48 nursing students from a Regional university in Korea. Data were collected in December 2023 through reflection journals completed by participants; these journals were analyzed using thematic content analysis. Results The analysis identified 10 subtopics, including four themes: (1) enhancing nursing skills for patients with pneumonia; (2) improving nursing communication skills; (3) creating a learning environment using VR technology; and (4) increasing awareness of nursing capabilities through VR. Conclusion By using VR, nursing students experienced a series of scenarios involving caring for patients with pneumonia. More diverse VR scenario developments and technical improvements are needed to enhance the competencies of prospective nurses.